Enhanced Cu(II) rejection and fouling reduction through fabrication of PEG-PES nanocomposite ultrafiltration membrane with PEG-coated cobalt doped iron oxide nanoparticle - Kian, Hwa Chan (Elsevier, 2015)
Membrane modified by adding nanoparticles coined as nanomodified membrane is another latest trend in membrane technology. This paper investigates the influence of polyethylene glycol (PEG) coated cobalt doped iron oxide (Co-Fe2O3) nanoparticles on the morphological and properties of (PES) ultrafiltration membrane (UF). The synthesized Co-Fe2O3 nanoparticles were coated with different concentrations of PEG solutions to prevent them from agglomeration and then added to the PES/DMF dope solutions. The performance of the nanomodified membranes was then compared to the control PEG/PES/DMF dope solutions in terms of flux rates and Cu(II) removal at various operating conditions. The antifouling properties were determined using bovine serum albumin (BSA) as the model foulant. Findings revealed that the Cu(II) removal efficiency of the nanomodified membranes was enhanced considerably (as high as 96%) and the antifouling properties improved. In order to obtain membranes with high Cu(II) removal and reasonable flux rates the concentration of nanoparticles must be kept at 6% but PEG coating concentration high (6-9%); with ratio of PEG coating to Co-Fe2O3 kept more than 1.0. (C) 2014 Taiwan Institute of Chemical Engineers.